Estudo químico, análise do óleo essencial e avaliação das atividades antioxidante e antibacteriana do Marmelhinho [Cordiera sessilis (Vell.) Kuntze (Rubiaceae)] - Canelhas, Brunno Borges (2012)
In this work was carried out chemical analysis, identification of volatile components, the determination of antioxidant activity and antibacterial activity of wood, bark and leaves of Cordiera sessilis (Vell) Kuntze, known as marmelinho. This study is justified because the analysis of chemical species Cordiera sessilis (Vell) Kuntze had not been studied so far. Ethanol extracts of leaves, bark and wood were prepared and subjected to chemical analysis, seeking to identify, quantify and therefore determine the applicability of vegetable medicinal use. The percentages obtained for the macromolecular constituents of the bark and wood are within the acceptable range for hardwood trees. The content of Klason lignin was found to be 28.55 % and 24.00 % holocellulose content was 20.0 % and 72.0 % for the shell and timber, respectively. This work presents the first identification by gas chromatography-mass spectrometry (GC-MS) of essential oil from leaves, bark and wood. 31 were identified components for the sheets, in most organic acids, totaling 46 % of oil, especially the n-hexadecanoic acid (24.73 %) and linolenic acid (6.91 %). Linalool, α-Terpineol, (E)-Geraniol and Phytol were only found oxygenated monoterpenes and diterpenes respectively, corresponding to 5.84 % of total oil. Even if include short chain alcohols (such as cyclohex-4-en-1-ol, hex-3-en-1-ol, Hex-2-en-1-ol, 1-hex-1-anol ), totaling 23 % of oil, and aldehydes (such as (E)-2-hex-2-enal (5.31 %)), totaling 12 % of total oil. To the shells 18 have identified components, the majority of long chain fatty acids, total 88.4% of oil, especially the hexadecanoic acid (40.11 %) and octadecadienoic acid (33.2 %). In the wood was identified 18 components, we have again the predominance of long chain fatty acids, especially hexadecanoic Acid (32.23 %) and n-nonadecanoic acid (18.53 %), and this time was found sesquiterpene trans-Caryophyllene (0.72 %). For analysis of total phenols by Folin-Ciocalteau found 42.12 ± 0.93 mg g-1 sample to the leaves and 35.23 ± 0.46 mg g-1 sample to the shells. The content of proanthocyanidins found by the method of Vanillin was 133.6 ± 0.021 mg ECAT g -1 sample to the sheets and 111.1 ± 0.023 mg ECAT g-1 sample for the peel. In determining the antioxidant activity of EC50 values found for the leaves were 38.94 ± 2.59 mg mL-1 for the crude ethanolic extract, 79.67 ± 4.19 mg mL-1 for cyclohexane partition, 38.165 ± 5, 92 mg ml-1 for the partition dichloromethane, 17.97 ± 2.72 mg mL-1 to the partition ethyl acetate, and 15.79 ± 1.017 mg ml-1 for the partition methanol. As for the shells found EC 50 values are 39.73 ± 5.01 mg mL-1 for crude ethanol extract, 415.55 ± 0.83 mg mL-1 for the partition cyclohexane and 33.24 ± 0.75 g ml-1 for the partition dichloromethane. The extracts from the leaves and barks and its partitions showed antibacterial activity against the micro-aerobic and anaerobic organisms, especially the partitions in cyclohexane and dichloromethane leaf with values of minimum inhibitory concentrations (MIC) of 50 mg mL-1 for anaerobic micro-organisms. The partition of cyclohexane shells with MIC of 25 mg ml-1 and the other partitions of the leaves had minimum inhibitory concentrations ranging from 200 to 400 mg mL-1 for aerobic micro-organisms, and values between 100-400 mg ml-1 for micro anaerobic organisms. The partitions shells ranged from 25-400 mg ml-1 for the aerobic and anaerobic for the values are higher than 400 mg mL-1. Compared with other studies of cerrado plants MIC values for the extracts and partitions of the leaves are considered very relevant to the continuing search for other characterizations.